Vitamin C in the Presence of Sub-Inhibitory Concentration of Aminoglycosides and Fluoroquinolones Alters Proteus mirabilis Biofilm Inhibitory Rate - Joanna Kwiecińska-Piróg; Krzysztof Skowron; Tomasz Bogiel; Agata Białucha; Jana Przekwas; Eugenia Gospodarek-Komkowska (MDPI AG, 2019)
Vitamin C has antimicrobial activity and is often used as an oral supplement accompanying antibiotic treatment in urinary tract infections (UTI). Proteus mirabilis is the third common species responsible for UTIs that are mostly treated with fluoroquinolones or aminoglycosides. Treatment of the UTI caused by P. mirabilis is problematic due to the ability to form biofilm on the urinary catheters. The aim of the study was to evaluate the influence of ascorbic acid in combination with antibiotics on P. mirabilis abilities to form biofilm. The susceptibility of P. mirabilis reference strain ATCC® 29906™ and four clinical strains isolated from the urine samples of patients with urinary catheter were evaluated according to EUCAST recommendations. The influence of ascorbic acid (0.4 mg × mL−1) in combination with antibiotics on biofilm formation was evaluated spectrophotometrically. Aminoglycosides at sub-inhibitory concentrations more successfully limited biofilm formation by P. mirabilis strains without ascorbic acid addition. Inhibition rate differences at the lowest concentrations of gentamicin and amikacin were statistically significant (p ≤ 0.05). Ascorbic acid addition to the culture medium limited the inhibitory effect of fluoroquinolones, facilitating biofilm formation by P. mirabilis strains. The addition of ascorbic acid during aminoglycosides therapy may disturb treatment of urinary tract infections related to the presence of P. mirabilis biofilm.